WHO YOU ARE ISN'T WHO YOU WILL BE. Issue 83 (January 2017) - Kouzes, Jim; Posner, Barry
Abstract : Kouzes and Posner focus on the future‐oriented aspect of leadership, envisioning and creating a better future for leaders and their organizations. However, they do not neglect the here‐and‐now: "As counterintuitive as it might seem, the best place to start creating the future is by being more mindful in the present." Leaders must consciously develop the capacity to be observant and to listen for what matters. For instance, they write, "You need to envision your ideal self. You need to have a vivid image of the very best person you could become, achieving goals you cherish, living congruently with your values, having fulfilling relationships, and making a positive difference in the world."